2021
DOI: 10.3389/fneur.2021.741754
|View full text |Cite
|
Sign up to set email alerts
|

Atherogenic Index of Plasma Predicts Outcomes in Acute Ischemic Stroke

Abstract: Aim: The atherogenic index of plasma (AIP) was significantly related to adverse outcomes in patients with cardiovascular disease. Our aim was to investigate the association between AIP and adverse outcomes in acute ischemic stroke.Methods: Patients with acute ischemic stroke (AIS) admitted between 2015 and 2018 were prospectively enrolled in this study. Functional outcomes were evaluated by the modified Rankin Scale (mRS). Poor outcomes were defined as mRS 3–6. The relationship of AIP with the risk of outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 38 publications
2
28
0
Order By: Relevance
“…Hence, NAFLD patients present an increased CV risk [ 21 , 22 , 23 ]. The atherogenic index of plasma (AIP), a novel quantitative index utilized to assess lipid levels, is a strong marker of dyslipidemia [ 24 , 25 ]. The logarithmic ratio between triglyceride levels and HDL-C yields the AIP, which indicates the association between atherogenic and protective lipoprotein [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, NAFLD patients present an increased CV risk [ 21 , 22 , 23 ]. The atherogenic index of plasma (AIP), a novel quantitative index utilized to assess lipid levels, is a strong marker of dyslipidemia [ 24 , 25 ]. The logarithmic ratio between triglyceride levels and HDL-C yields the AIP, which indicates the association between atherogenic and protective lipoprotein [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…A secondary analysis of the Action to Control Cardiovascular Risk in Diabetes (ACCORD) study showed AIP was an independent risk factor among the patients with type 2 diabetes mellitus AIP 28 . A recent registry study revealed that AIP could be associated with the outcome of dysfunction in patients with acute ischemic stroke, and this study also further evaluated the predictive values of blood lipid and found AIP was the best discriminating variable to predict poor outcomes, death, and disability 29 . In line with those past studies, our study of 98 861 participants with significant statistical power showed that the quartile 4 group of the baseline AIP had a 1.98-fold higher risk of MI compared with the quartile 1 group, and this significant association of a higher risk of MI in the quartile 4 group persisted after adjusting all potential covariates.…”
Section: Discussionmentioning
confidence: 86%
“…27 AIP may be a reliable indicator of acute ischemic stroke, particularly the stroke subtype of large-artery atherosclerosis. 28 According to Kim et al, high AIP predicts IHD in non-diabetic Koreans. As an alternative to isolated TG levels or other lipid markers, AIP is increasingly used to stratify distinct cardiometabolic risks.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%